Biologic variation of symmetric dimethylarginine and creatinine in clinically healthy cats - Prieto, Jennifer M.; Carney, Patrick C.; Miller, Meredith L.; Rishniw, Mark; Randolph, John F.; Farace, Giosi; Bilbrough, Graham; Yerramilli, Maha; Peterson, Mark E. (Veterinary clinical pathology, 2020)
Background Biologic variation of biochemical analytes, both within individuals and between individuals, determines whether population‐based reference intervals (RIs) are appropriate when interpreting if a particular change is clinically relevant for a specific individual. Objectives We aimed to evaluate the biologic variation of symmetric dimethylarginine (SDMA) in clinically healthy cats. Methods A prospective, observational study was performed in which 10 clinically healthy, client‐owned cats were sampled for serum biochemical analyses once weekly for 6 weeks. Serum samples were frozen, and then single batches were analyzed for SDMA, using both liquid chromatography‐mass spectroscopy (LC‐MS), and an enzyme multiplied immunoassay technique (EMIT), and creatinine by modified Jaffe method. Restricted maximum likelihood estimations were used to determine the coefficients of variation (CVs) describing variation within each cat, between cats, and the analytical variation. These CVs were used to determine the indices of individuality and reference change values (RCVs). Results SDMA had an intermediate index of individuality that could be evaluated by both RCV and population‐based RIs. In contrast, creatinine had a high index of individuality best evaluated with RCVs. Serum SDMA concentrations evaluated with either the reference standard, LC‐MS, or the clinically used EMIT yielded similar results. Conclusions Clinicians should consider biologic variation when selecting the best method for interpreting changes in biochemical analytes. Specifically, establishing each cat's baseline serum creatinine and SDMA concentrations during health, and applying RCVs to subsequent measurements could improve the recognition of meaningful biologic changes.